Parasitoidismo por dípteros en larvas de Caligo atreus (Lepidoptera: Nymphalidae) en Cartago, Costa Rica - Calvo, Renán (Universidad de Costa Rica, 2004)
Parasitoids on larvae of Caligo atreus were studied at the Estación de Biología Tropical in Río Macho, Cartago, Costa Rica. (1 600 masl), from March through July 2000. Fifth instar larvae of C. atreus were placed on Heliconia tortuosa Griggs var. Red Twist (Heliconiaceae) host plants at a mean temperature of 16.7°C. The parasitoids obtained belong to an unidentified species of the genus Winthemia (Diptera: Tachinidae). Most flies emerge some 40 days after the eggs were laid (maximum 68 days). They make an orifice on the upper ventral part of the lepidopteran pupa. Winthemia is used commercially as biological control of cotton and banana.